2017
DOI: 10.1177/0033294116685867
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Loving-Kindness Meditation

Abstract: An experiment involving 115 undergraduate students (74.8% females; mean age = 20.5 years, SD = 4.3) was conducted to explore effects of meditation on social connectedness, nature connectedness, and affect. Participants listened to one of three brief guided meditation Mp3 recordings via the internet, which involved mindfulness meditation (MM), loving-kindness meditation (LKM), or progressive muscle relaxation (active control group). Participants in the MM and LKM groups reported greater social and nature connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…Yet in our sample, happiness and CWN showed to be greater even for those with limited mindfulness practice, somewhat moderating the assumption that the development of greater psychological well-being depends on the extent of engagement with the practice (Carmody and Baer, 2008). Our results also reflect experimental research by Aspy and Proeve (2017) who showed that even after a short meditation exercise, CWN increased significantly. Overall, our results indicate that mindfulness, subjective happiness and CWN might be interrelated and practice dependent (Howell et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Yet in our sample, happiness and CWN showed to be greater even for those with limited mindfulness practice, somewhat moderating the assumption that the development of greater psychological well-being depends on the extent of engagement with the practice (Carmody and Baer, 2008). Our results also reflect experimental research by Aspy and Proeve (2017) who showed that even after a short meditation exercise, CWN increased significantly. Overall, our results indicate that mindfulness, subjective happiness and CWN might be interrelated and practice dependent (Howell et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…Yet, we could show that the weak relationship between mindful compassion practice and GHG emission reductions was partially mediated by relational factors, particularly by CWN but also a more internalized motivation for PEB. While previous studies have shown a reciprocal relationship between dispositional mindfulness and CWN (Schutte and Malouff, 2018), little evidence exists regarding the impact of the practice of mindfulness on CWN (Aspy and Proeve, 2017). Furthermore, our mediation analysis indicates that mindful compassion practice could be effective as an experiential strategy that strengthens the relational pathway of PEB and therefore deepens the motivation toward the environment (Thiermann and Sheate, 2020a).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Unpacking this further, it is possible that greater time spent in nature provides recurrent and sustained opportunities to develop greater trait mindfulness (see Duvall, 2011aDuvall, , 2011bPassmore & Holder, 2017). In turn, the non-judgemental awareness that is a core component of mindfulness may allow individuals to more fully engage with nature and thus develop greater connectedness to nature (Aspy & Proeve, 2017;Hanley et al, 2020;Schutte & Malouf, 2018;Unsworth et al, 2016). That is, the ability to regulate attention on present-moment experiences -rather than the capacity to observe experiences non-judgementally -appears to be key in terms of the relationships between nature exposure, connectedness to nature, and body image.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, greater trait mindfulness has been shown to be significantly associated with connectedness to nature (weighted effect size of r = .25; Schutte & Malouf, 2018). In particular, the non-judgemental awareness that is central to trait mindfulness may allow individuals to fully engage with nature, thus helping to promote greater connectedness to nature (e.g., Aspy & Proeve, 2017;Hanley, Bettmann, Kendrick, Deringer, & Lynn Norton, 2020;Unsworth, Palicki, & Lustig, 2016). In short, there are reasons to think that the relationship between nature exposure and positive body image may be serially mediated by trait mindfulness and connectedness to nature, respectively.…”
Section: Introductionmentioning
confidence: 99%